Onna jūni-dai : Torii Kiyotada bijin hanga. dai 1-kai hanpu Kamisuki. - Torii, Kotondo, 1900-1976 ([Tokyo] : [publisher not identified], 1980)
The Japanese print depicts a young woman in kimono combing her hair.
Title from cover. First printing date are known as 1980.
Printmaker's signature and seal present on print.
Horishi Itō Susumu; surishi Kajikawa Yoshio.
Keywords: Young women -- Japan -- Pictorial works; Woodblock prints